Competency and strategy parameters selection based on fuzzy-based modelling for Indian automobile industries. (24th February 2020) - Singh, Chandan Deep
The automobile manufacturing units need to create their own core competencies in order to survive in the fiercely competitive market. A core competency is an internal capability that is critical to the success of business. It should provide organisations with significant performance enhancements and should fulfil three attributes: it should offer customer advantages, it should be difficult for competitors to replicate and it should find applications wide variety of products and markets. This paper presents fuzzy-based modelling for competency and strategy parameters.